Subcellular localisation of cholesterol and phosphocholine with pattern-recognition-imaging-TOF-SIMS. Issue 4 (2004) - Malmberg Malmberg, Per Per; Nygren Nygren, Håkan Håkan; Sjövall Sjövall, Peter Peter; Lausmaa Lausmaa, Jukka Jukka
Abstract : Molecular ions of cholesterol, and its fragments, and phosphocholine fragments of phospholipids, were localized in single cells with a resolution of <1 μ m. This is the first example of subcellular localisation of membrane lipids with pattern-recognition, imaging time-of-flight secondary ion mass spectrometry (PRITS) here utilized for identification and subcellular localisation of cholesterol and phosphocholine in PMN leukocytes. Cell imprints were produced by transferring the cell constituents of freeze-dried cells to a silver foil, and the silver surface was analyzed by TOF-SIMS. TOF-SIMS spectra were recorded by scanning the primary ion beam over the analysis area and acquiring a positive mass spectrum of the ions leaving the surface. Data were collected at either high mass resolution m/ Δ m > 7000 or high lateral resolution. High mass resolution spectra were recorded on reference samples of pure cholesterol and phosphatidylcholine. Characteristic fragment peaks and the silver cationised quasimolecular ion [M+Ag] + were selected as a pattern for the identification of the lipids in TOF-SIMS images of surface-adhering leukocytes. The localisation of membrane lipids showed lateral heterogeneity over the cell surface.